Signaling Pathways of Type I and Type III Interferons and Targeted Therapies in Systemic Lupus Erythematosus - I-Tsu Chyuan; Hong-Tai Tzeng; Ji-Yih Chen (Cells, 2019)
Type I and type III interferons (IFNs) share several properties in common, including the induction of signaling pathways, the activation of gene transcripts, and immune responses, against viral infection. Recent advances in the understanding of the molecular basis of innate and adaptive immunity have led to the re-examination of the role of these IFNs in autoimmune diseases. To date, a variety of IFN-regulated genes, termed IFN signature genes, have been identified. The expressions of these genes significantly increase in systemic lupus erythematosus (SLE), highlighting the role of type I and type III IFNs in the pathogenesis of SLE. In this review, we first discussed the signaling pathways and the immunoregulatory roles of type I and type III IFNs. Next, we discussed the roles of these IFNs in the pathogenesis of autoimmune diseases, including SLE. In SLE, IFN-stimulated genes induced by IFN signaling contribute to a positive feedback loop of autoimmunity, resulting in perpetual autoimmune inflammation. Based on this, we discussed the use of several specific IFN blocking strategies using anti-IFN-α antibodies, anti-IFN-α receptor antibodies, and IFN-α-kinoid or downstream small molecules, which intervene in Janus kinase (JAK)-signal transducer and activator of transcription (STAT) pathways, in clinical trials for SLE patients. Hopefully, the development of novel regimens targeting IFN signaling pathways will shed light on promising future therapeutic applications for SLE patients.